Algorhythmics and Media Concepts: Ada Lovelace's Notes to "Sketch of the Analytical Engine". - Whitson, Roger (Victorian Studies)
Ada Lovelace's notes to Luigi Menabrea's "Sketch of the Analytical Engine" (1843) constitutes a significant development in the history of what John Guillory calls "the media concept." Standing in contrast to her mentor Charles Babbage, who saw mediation as that which is in between input and output, Lovelace distinguishes the material operation of the machine from the digital simulation performed by its manipulation of numbers. Her image of computing is a musical composition, in which mathematical processes are seen as various materials and temporalities orchestrated together. I link Lovelace's work to the "algorhythmics" of Shintaro Miyazaki and the "time-criticality" of Wolfgang Ernst. I also perform a grammatological analysis of her program for computing Bernoulli numbers as a demonstration of how she sees the distinct but orchestrated domains of material and number working together. The Bernoulli program, along with her reflections on the media implications of the Analytical Engine, enabled Lovelace to develop her own media concept decades before the publication of Walter Benjamin's "The Work of Art in the Age of Mechanical Reproduction" (1935).